2003
DOI: 10.1352/0895-8017(2003)108<0149:rlsoaa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Receptive Language Skills of Adolescents and Young Adults With Down or Fragile X Syndrome

Abstract: We investigated the receptive language of adolescents and young adults with Down syndrome (n = 25) or fragile X syndrome (n = 19). We were interested in syndrome differences and gender differences within fragile X. Comparison of the syndromes and MA-matched typically developing children (n = 24) revealed that individuals with the syndromes differed in relative achievements across the domains of receptive vocabulary, receptive syntax, and nonverbal cognition as well as in the organization of their linguistic kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
2
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(147 citation statements)
references
References 35 publications
7
129
2
9
Order By: Relevance
“…Consistent with previous findings indicating higher language abilities in girls with FXS (Abbeduto et al, 2003;Finestack & Abbeduto, 2010;Pierpont et al, 2011), most girls in our sample demonstrated higher syntactic abilities than boys, although individual differences were noted. That is, only half of the female participants outperformed the male participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings indicating higher language abilities in girls with FXS (Abbeduto et al, 2003;Finestack & Abbeduto, 2010;Pierpont et al, 2011), most girls in our sample demonstrated higher syntactic abilities than boys, although individual differences were noted. That is, only half of the female participants outperformed the male participants.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the X-linked nature of the disorder, effects on girls tend to be moderated by the presence of a second X chromosome (Crawford, Acuña, & Sherman, 2001;Hagerman & Hagerman, 2002;Lachiewicz, 1995). In terms of language abilities, evidence indicates that girls are not as delayed as boys (Abbeduto et al, 2003;Finestack & Abbeduto, 2010;Fisch et al, 1999). Girls with FXS have generally demonstrated higher receptive (Abbeduto et al, 2003) and expressive (Finestack & Abbeduto, 2010;Finestack, Sterling, & Abbeduto, 2013;Sterling & Abbeduto, 2012) language skills, and tended to acquire specific language skills (i.e., vocabulary, syntax) faster over time than boys with FXS (Pierpont, Richmond, Abbeduto, Kover, & Brown, 2011), with the exception of a small proportion of girls who also have comorbid autism.…”
Section: Factors Related To Language Development In Fxsmentioning
confidence: 99%
“…Specitically, receptive language skills have been reported to grow at about half the rate of typically developing children, while expressive language skills were reported to increase at about one-third the rate of typical development owr time in young children with fragile X syndrome (Roberts et al,200 I). Furthermore, by young adulthood, receptive language has been reported to be mental-age appropriate in boys with tragile X syndrome who do not meet criteria for an autism spectrum disorder (Abbeduto et al, 2003).…”
Section: Fragile X Syndromementioning
confidence: 99%
“…Some of the speech difficulties reported in this population have: been a suggested function of a developmental dyspraxia of speech (i.e., difficulties related to the motor planning involved in speech sound production [Dykens et al, 1994;Abbeduto and Hagerman, 1997]. Although limited, syntactic usc studies of children with FXS haw suggested delays relative to MA-expectancies; however, receptive morpho-syntactic skills appear to be on par with mental age in school-age and adolescent boys [Paul et al, 1984;Abbeduto et al, 2003]. Fluency-related expressive difficulties have been noted in an increased number of dysfluencies, though it has been suggested that these dysfluencies are fewer than those observed in a stuttering disorder [Newell et al, 1983;Paul et al, 1984;Hanson et al, 1986;Wolf-Schein et al, 1987].…”
Section: Fragile X Syndromementioning
confidence: 99%
“…Deficits in vocabulary and morphosyntax have been identified in expressive and receptive modalities, although receptive language skills are generally stronger than expressive language skills (Chapman, Schwartz, & Kay-Raining Bird, 1991;Eadie, Fey, Douglas, & Parsons, 2002;Martin, Klusek, Estigarribia & Roberts, 2009). These deficits are particularly apparent in studies where children with DS are compared to peers with intellectual disabilities matched on mental age or IQ level (Abbeduto, Murphy, Cawthon, Richmond, et al, 2003;Chapman, 2006;Fidler, Hepburn, & Rogers, 2006, Roberts, Price, Barnes, Nelson, et al, 2007. Because vocabulary acquisition is a crucial element of language development in all children, but especially in those with delayed or inefficient language learning, additional research in the development of expressive and receptive vocabulary in children with DS is warranted.…”
mentioning
confidence: 99%